Studi Tafsir Tematik: Kajian Nanopartikel Menurut Al-Qur’an Serta Pemanfaatannya di Bidang Medis - Farah Fauzia Maulahibati; Umaiyatus Syarifah; Eko Budi Minarno (Es-Syajar:Journal of Islam, Science and Technology Integration, 2023)
Nanoparticles are small particles that can penetrate physiological barriers in the body and circulate in the circulatory system. Nanoparticles are very small, just like atoms, which cannot be seen directly by the eye and require a microscope to see them. Nanoparticles are made with a very small size to overcome difficulties in dissolving active substances, improve poor bioviability of compounds, and directly modify drug delivery systems to specific areas. The Qur'an does not specifically discuss nanoparticles, but the Qur'an explains it implicitly in the word zarrah which is repeated 6 times. The repetition of the word zarrah is in Q.S An-Nisa'/4 verse 40, Q.S Yunus/10 verse 61, Q.S Saba'/34 verse 3, Q.S Saba'/34 verse 22, and Q.S Al-Zalzalah/99 verses 7-8. This research method uses thematic interpretation, namely the method of interpretation through the collection of verses of the Qur’an with the same topic to be studied. Scholars and commentators interpret zarrah as a small seed or red ant head or something small in size. Modern commentators always associate zarrah with atoms because of their very small size. Along with the times, there is currently a new technology in the medical world that uses small particles such as atoms known as nanoparticles